Impacts of Agricultural Commodity on Road Transport at Selected Areas in Metro Manila: Vol.3, No.1C (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Transportation helps to bring stability to the price of different products. It transports goods from more supplied places to scarcely supplied areas. Thus, the economic growth of a country is necessary for the betterment of the people and an indication of a competitive country. Thus, transportation is a major component in the system of life, the system of government, and the social system.  It is also a big part of people’s daily living for it will give access and efficient travel from one place to another. The population density level will significantly affect the ability of transportation to serve community needs. Budi Manturo stated that the presence of the state to facilitate the movement of people and goods utilizing transportation, especially land transportation, is carried out as much as possible. In Metro Manila, one of the major problems of the business owner is the heavy traffic and the continuous rehabilitation of the road that cause them delayed. Products must be delivered on time to avoid contamination risk. Since most of the agricultural products in Metro Manila are from different provinces, having a good transport system is necessary to benefit business owners, consumers, and farmers.  Furthermore, transport is an essential component of tourism by definition, providing connections between regions, domestically and internationally, and connecting attractions, accommodation, and commercial services at destinations. Tourism is crucial in promoting national and regional economies but can pressure existing transport services and infrastructure. Without well-developed transportation systems, logistics could not bring its advantages into full play, and a good transport system performing in logistics activities benefits not only service quality but also company competitiveness.  Therefore, a good transportation system is necessary in a country. According to Ines Hajdu, an agronomy expert, the story of adequate farm management begins and ends with efficient and properly managed transport. The study will also determine the current state of the Metro Manila transport system. This study aimed to describe and find out the challenges used by the transport system in Metro Manila towards agricultural commodities and to determine its strategies for sustaining the growth and ensuring the safety and sanitation of the goods.